Implementation of Investigations into the Crime of Incest by the Biological Father Against the Child Incest - Safrizal W. Yantu; Fenty U. Puluhulawa; Avelia Rahmah Y. Mantali (Estudiante Law Journal, 2023)
The main problem in this research is the process of investigating criminal acts of incest committed by the biological father against the child in the jurisdiction of the East City Police. biological father of the child at the East City Police. The aim of the research is to find out and explain the implementation and investigation of criminal acts of incest committed by the biological father against the child (Incest) at the East City Police. The results of the research are that the process of investigating the criminal act of incest by the biological father against the child is carried out in stages, making a report, conducting an investigation, carrying out a Visum et Repertum, sending a letter notifying the start of the investigation, conducting examination of witnesses, carrying out a case title to determine the suspect, carrying out coercive measures, examination of suspects, collection of evidence, filing.